العلاقة بين حفظ القرآن ونواتج تعليم اللغة العربية عند طلاب مدرسة العالية الاسلامية المتكاملة الهجرة 2 ديلي سردانج - Nur Azizah Harahap; Harun Al Rasyid (Universitas Nusantara PGRI Kediri, 2024)
This paper aims to find out about the relationship between Qur'an memorization and Arabic learning outcomes in IT Al-Hijrah Deli Serdang High School students. The method used in this research is field research method (Field Research) using quantitative approach. Data collection techniques using observation, interviews and documentation. The population in this study amounted to 22 students and sampling using saturated samples or all members of the population were used as research samples. The data analysis technique uses the Produck Moment Correlation test with the help of SPSS version 26. The result of this study is that memorizing the Qur'an has a significant and very strong relationship with Arabic learning outcomes. This can be seen from the Pearson Correlation value of 0.802. obtained t count 5.998 greater than t table (2.086) at a significant level of 5% and a significant level of 1% (2.845), then Ha is accepted and Ho is rejected. This means that there is a significant relationship between Qur'an memorization and Arabic learning outcomes in Al-Hijrah 2 Deli Serdang IT High School students.